A case study on the impact of section 10(1)(o)(ii) of the South African Income Tax Act on South African Expatriates - Forbes, Nicole (University of the Witwatersrand, Johannesburg, 2023)
Globalisation has triggered the onset of the migrant work force, which in turn, has created complexities with regards to striking a fine balance between preventing tax spill overs in relation to potential double taxation and remaining tax competitive in order to retain and attract South African tax residents (De Koker & Brincker, 2010; Fuest, Huber, & Mintz, 2005; Spengel & Fischer, 2022). SouthAfrica taxes residents on their worldwide income, and on 1 March 2020, section 10(1)(o)(ii) of the Income Tax Act 1962 (hereafter referred to as “the Act”) was amended with the objective of addressing tax disparities in respect of taxes being levied on remuneration earned from a local source versus internationally, through limiting tax relief to R1, 250,000 for foreign-derived remuneration (Africa, 2021; De Koker & Brincker, 2010; Ferreira, 2020; Govender, 2019; Hutchon & Kim, 2020; Naidoo, 2019; SARS, 2021a, 2021c; Sebashe, Erasmus, & Erasmus, 2021). This discussion-based research report evaluates the impact of the amendment to section 10(1)(o)(ii) in relation to foreign remuneration earned by South African expatriates. Similar to prior research, conducted by Govender (2019), Naidoo (2019) and Sebashe et al. (2021), this research report draws comparisons amongst South African expatriates earning employment income from (i) the United Arab Emirates (UAE), where no personal income tax is currently levied (PwC, 2022c); (ii) the United Kingdom (UK), where non-residents are entitled to a personal allowance, i.e. tax relieve of GBP 12,500 for the 2020/2021 tax year if their UK sourced taxable income is less than GBP 100,000 (Gov.UK, 2022) and (iii) the United States of America (USA), where non-residents or alternatively termed ‘non-resident aliens’, are not entitled to a standard personal tax deduction (PwC, 2022g). The comparative case studies aim to assess whether or not the revised and promulgated section 10(1)(o)(ii) has aided in restoring fairness in the levying of tax, through contrasting i) pre 1 March 2020 tax treatment of section 10(1)(o)(ii), i.e. one hundred percent exemption of foreign remuneration and ii) 1 March 2020 tax treatment of section 10(1)(o)(ii), the introduction of “expat taxation” (Africa, 2021; De Koker & Brincker, 2010; Ferreira, 2020; Govender, 2019; SARS, 2021c; Sebashe et al., 2021). In addition, this report evaluates the impact of through (i) double tax agreements (DTAs); (ii) section 6quat of the Act; (iii) personal allowances/reductions and (iv) change in tax residency on a South African expatriate’s overall local personal tax position (the impact discussed, but not specifically evaluated in the case study computations) (De Koker & Brincker, 2010; Ferreira, 2020; Govender, 2019; Hutchon & Kim, 2020; Sebashe et al., 2021). Furthermore, the report assesses the impact of the revised and promulgatedsection 10(1)(o)(ii) on the low, moderate and high remuneration earners, in accordance with prior research conducted by Sebashe et al. (2021), the aim is to assess whether or not the amended to expat tax exemption, namely, the introduction of the R1,250,000 exemption threshold, had an adverse effect of the local tax positions of low and moderate foreign remuneration earners
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce specialising in the field of taxation, University of the Witwatersrand, Johannesburg, 2023
Keywords: Section 10(1)(o)(ii); Section 6quat; Double tax agreements; Tax law United States of America; Tax law United Arab Emirates and tax law United Kingdom; Residency; UCTD; SDG-8: Decent work and economic growth